Comparison of three antimicrobial strategies in diabetic foot infections post-amputation. (July 2019) - Shah, Samarth P.; Negrete, Ana; Self, Timothy; Bergeron, Jaclyn; Twilla, Jennifer D.
Background: The 2012 Infectious Disease Society of America (IDSA) guidelines recommend antimicrobial treatment of diabetic foot infections (DFIs) post-amputation, but the optimal route and duration are poorly defined. Objective: The objective of this study was to determine whether the selection of a specific antimicrobial treatment modality affected hospital and patient outcomes. Methods: This was a retrospective review of hospital admissions of adults admitted to ourhealthcare system with a primary diagnosis of DFIs post-amputation. The groups were separated into patients who received intravenous antimicrobials (IV), oral antimicrobials (PO), or no antimicrobials (NA). Outcomes included average length of stay among others. Results: Of the 200 patients screened, 120 patients were included (IV n = 72; PO n = 20; NA n = 28). No statistically significant differences were identified in average LOS (IV = 9.97 ± 5.85, PO = 8.83 ± 7.37, NA = 9.33 ± 5.91 days; p = 0.73). However, post-operative (post-op) LOS was significantly shorter in the PO group (PO = 3.43 ± 2.56, IV = 7.34 ± 5.95, NA = 5.81 ± 4.18 days; p = 0.0001). Conclusion: The results of our study indicate that a PO antimicrobial treatment strategy post amputation for DFIs has the potential to decrease post-op LOS without increasing the risk of readmission. Based on the results of our study, we feel consideration should be given to transition to oral antimicrobials soon after amputation to facilitate discharge and decrease the utilization of intravenous antimicrobials.